الدفاع البلاغي في المرافعات القضائية - شعير, عماد (جامعة الوادي - University of Eloued, 2019)
يرتجي البحث الكشف عن كنه العلاقة بين البلاغة والخطاب القانوني لا سيما المرافعات، ودور البلاغة الفاعل في توطين الدعاوى وتأسيس الحجج، بوصفها أداة دفاع ماتعة في إماطة الدعاوى التقابلية وتحطيمها، والكشف عن مدى إسهام البلاغة العربية في التوطئة لذاك التوجه، وكيف وظفت التقنيات البلاغية لتكون أداة صد وهجوم في الآن، وركيزة في تشكيل الخطاب القانوني الدفاعي، ومدى استجابة القاضي والخصم لتلك الآليات؛ وذلك من خلال التطبيق على المرافعات المصرية لا سيما مرافعة محمد سليم العوا "المعروفة بخلية حزب الله 2010". Abstract: The research seeks to explore the relationship between rhetoric and legal discourse, especially pleadings and the active role of rhetoric in settling claims and establishing arguments as a powerful tool of defense that tends to refute and disprove counter-claims. The research further aims to reveal the extent to which Arabic rhetoric contributes to the settlement of this orientation, and how rhetoric techniques were simultaneously adopted as defensive and offensive tools and a pillar in the formation of the legal discourse of defense. It also attempts to investigate the extent of the judge's and opponent's responses to those mechanisms through application on the Egyptian pleadings, especially that of Mohammed Saleem Al'Awa, known as Hezbollah cell 2010.
مقال
Keywords: بلاغة- خطاب -الدفاع- قضائية - مرافعات; Defense –Discourse- pleadings – proceedings- Rhetoric.